Assessment knowledge and practices of central line insertion and maintenance in adult intensive care units at a tertiary care hospital in Saudi Arabia. Issue 11 (November 2020) - Almahmoud, Rasha S.; Alfarhan, Maha A.; Alanazi, Walaa M.; Alhamidy, Farah K.; Balkhy, Hanan H.; Alshamrani, Majid; El-Saed, Aiman; Sairafi, Betule A.; Bahron, Salim A.
Abstract: Background: Awareness of central line bundle by healthcare workers (HCWs) is essential for preventing catheter-associated bloodstream infections (CLABSI). The objective was to assess the knowledge and practice of insertion and maintenance central line bundles among HCWs in intensive care units (ICUs). Methods: A cross-sectional study was conducted at King Abdul-Aziz medical city in Riyadh between November 2017 and April 2018. The target was nurses and physicians working in three ICUs. The knowledge and practice were assessed using a structured study questionnaire that included also demographic characteristics. Results: A total 171 nurses and 41 physicians were included in the current analysis. More than 90% of HCWs correctly answered 9 out of 12 knowledge questions, specially questions related hand hygiene, maximal barrier, daily assessment, and dressing change. The overall knowledge score was 82% and was significantly higher among those who received central line bundle training. Self-reported compliance (all or most of the time) with 10 different bundle recommendations ranged between 50% and 97%, being highest with hand hygiene, maximal barrier, and using chlorhexidine (97% each) and lowest with using the subclavian site (50%). The overall self-reported compliance score was 87% and was significantly higher among nurses. There was weak positive correlation between knowledge and practice (correlation coefficient 0.266, p  = 0.001). Conclusion: Knowledge and compliance of central line bundle were generally high in our HCWs. Training is important in improving knowledge of central line bundle. Future educational activities should focus on specific compliance deficiencies such as using the subclavian site and dressing change.